Routing framework and creation algorithm in Ad Hoc based SDN - Fang DONG; Yuxiang HU; Ou LI (Tongxin xuebao)
Node energy-limited and mobility,indeed,requirement of customized service,made Ad Hoc press for customization Routing.Based on the core principle of software defined networking (SDN),the control framework and the design of routing creation bran-new approach about Ad Hoc based SDN was analyzed firstly.Secondly,the hierarchical routing model was established,and the problem of routing key nodes and key link centralized selection based on service path was proposed and its algorithm was designed,which could embed customize service into physical networks via nodes mapping based network performance maximization.Finally,it corroborate the advantage of routing implement via SDN in function,performance and the whole networks utilization.Experiments show that the energy consumption of network nodes is more balanced and the overall utilization of the network is nearly 14% higher than the traditional method.